Assessment of knowledge, attitude and practice towards diabetes among type 2 diabetes patients in rural Mysuru - Suresh, Nishchitha; D., Sunil Kumar; N., Chandan; M. R., Narayan Murthy (International Journal Of Community Medicine And Public Health, 2021)
Background: Type 2 diabetes mellitus is considered one of the most frequent disease in the world. Diet and its practice, sedentary way of life are the key factors for rapidly rising incidence amongst developing countries. It is better controlled when people are aware of the pitfalls of the condition and improve their nutritional knowledge, attitude, and habits as a whole. As well, as to encourage patients to improve their diet, an appropriate self-care practice and to enhanced a good quality of life. Methods: Across sectional study was conducted at rural primary health center, suttur, Mysore. Type 2 diabetes (having for >1 years) aged between 18-70 years formed the study population and whose consented were interviewed in details to understand their knowledge, attitudes and practice regarding diabetic diet, risk factors and symptoms. Analysis performed using IBM SPSS 23.0. Results: A total of 384 participants took part in study. The mean knowledge, attitude and practice scores were 3.15±1.84, 1.66±0.927 and 3.65±0.488, respectively. Among the study participants, 192 (50%), 269 (70.1%) and 248 (64.6%) had good knowledge, attitude and practices towards diabetes. Conclusions: It is one such type of disease which can be prevented at various levels by identifying predictors like BMI, physical activity, quantity of sleep, etc. Diabetic patients had poor dietary practices and consumed protective foods inadequately. Still there is a lot of gap in their knowledge, attitude and practice on diabetes which have to be addressed them by educating them.